UNDERGRADUATE STUDENTS PERCEPTIONS’ ANALYSIS ABOUT DIFFICULTIES IN ENGLISH SPEAKING - Laila Desnaranti; Febby Pratama Putra (Universitas Indraprasta PGRI, 2022)
English as the most widely used language in the world is learned by undergraduate students, both who are majoring in English and those who are not majoring in English. English speaking skill is an important skill because it is needed in order to have a conversation to communicate but mastering English speaking skills is not easy. The purpose of this research was to determine undergraduate students' perceptions of difficulties in speaking English, especially undergraduate students majoring in non-English languages.This study used a qualitative descriptive method with data analysis techniques based on the results of interviews with informants and through a questionnaire conducted to 67 undergraduate students. The results of the study indicate that there are psychological, social, lecturer, and linguistic factors that cause students to have difficulty speaking in English. If the undergraduate students have a perception of what difficulties they face to be able to master English speaking skills then they will be able to find solutions to overcome these difficulties. This will help them in improving their English speaking abilities